2007
DOI: 10.3923/ijps.2007.679.683
|View full text |Cite
|
Sign up to set email alerts
|

Pathological Findings of Highly Pathogenic Avian Influenza Virus A/Duck/Vietnam/12/2005 (H5N1) in Turkeys

Abstract: The aim of present study was to identify the clinical signs, gross and histopathological findings in turkeys experimentally infected with highly pathogenic avian influenza virus A/duck/Vietnam/12/2005 (H5N1). Specific pathogens free of white turkeys having 6 weeks old were inoculated with 0.1 mL of the virus with 10 EID. Death was event at 3 DPI. Gross lesions observed after necropsy were splenomegaly, 5 50 pulmonary edema, severe congestion in lungs, hyperemia in brain as well as cecal-tonsil and congestion i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Perkins et al, (2003) traced influenza virus serotype H5N1 in spleen tissue and reported that in 2 or 5 days after inoculation, viral antigens were cloned in histiocytosis of the spleen and induced histiocytosis, endothelial cells, and myocytes of spleen arterial straight muscle death [10]. Mehranpour et al, (2007) studied the effects of the H5N1 virus in turkeys and showed that the main damages happened in brain, pancreas and tonsil cecum [5]. The results of the present study were consistent with Mangkol, Roberto, Perkins, and Mehranpour and the role of the H9N2 virus in damaging lymphoid tissue were explained.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Perkins et al, (2003) traced influenza virus serotype H5N1 in spleen tissue and reported that in 2 or 5 days after inoculation, viral antigens were cloned in histiocytosis of the spleen and induced histiocytosis, endothelial cells, and myocytes of spleen arterial straight muscle death [10]. Mehranpour et al, (2007) studied the effects of the H5N1 virus in turkeys and showed that the main damages happened in brain, pancreas and tonsil cecum [5]. The results of the present study were consistent with Mangkol, Roberto, Perkins, and Mehranpour and the role of the H9N2 virus in damaging lymphoid tissue were explained.…”
Section: Discussionmentioning
confidence: 99%
“…There is proven evidence of intensification of pathogenic effect of a H9N2 strain of influenza virus A separated from chickens in China by co-infections caused by golden staphylococcus and Haemophilus paragallinarum [5]. Developing our knowledge about the ways that influenza viruses interact with the host cells at the cell surface and the mechanisms and the pathways to induce cell death in the host helps us to find more efficient ways to deal with the disease.…”
Section: An Experimental Study On Apoptosis In Lymphoid Tissues Of Spf Chicken After Avian Influenza Serotypes H9n2 Infectionmentioning
confidence: 99%
“…The challenge virus (GenBank accession number CY016883) was characterized (Beato et al, 2007) and belongs to clade 2.3.2 (WHO, 2016). The virus was also characterized by its phenotype in turkeys (Mehrabanpour et al, 2007) and ducks (Beato et al, 2007). The diluted challenge virus was not back-titrated.…”
Section: Methodsmentioning
confidence: 99%